Physical activity and erectile dysfunction: a systematic review - Camila Araujo; Melissa Souza; Aline Fernandes; Andreia Pelegrini; Alexandro Andrade; Adriana Guimarães (Revista Brasileira de Atividade Física e Saúde)
Defined as the constant or recurrent inability to attain or maintain a satisfactory erection, erectile dysfunction (ED) has multifactorial causes. Regular physical activity can be used as a preventive tool for ED. In this sense, the main objective of this study was to analyze the scientific literature, published in the last ten years (2004-2014), about the relationship between physical activity, ED and the associated factors among men older than 17 years in cross-sectional studies, randomized clinical trials and cohort studies. A systematic review was performed in articles published in the Bireme, ScienceDirect, and PubMed/Medline databases, in the SciELO electronic library and in the Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES) Journal and written in Portuguese, English and Spanish. A total of 230 studies were identified, and only 19 met the inclusion criteria, all of which were published in English. ED was diagnosed in all studies. Concerning physical activity, 17 studies identified a significant association with a lower incidence of ED, including cross-sectional and quasi-experimental studies and randomized clinical trials. ED appeared to be associated with different factors related to men’s lifestyle, particularly their level of education, non-communicable chronic diseases, body mass index and age.